Melayu: roots of identity. - Siti Soraya Syafawati Salim. (2008)
The project culminates in a coffee-table book, Melayu: Roots of identity. The entire process of making the book is summarized in this report, which details as well the background behind the theme of my book and the valuable insights gained from doing this project.